C1 metabolism plays an important role during formaldehyde metabolism and detoxification in petunia under liquid HCHO stress - Zhang, Wei (Plant physiology and biochemistry : PPB, 2014)
Copyright © 2014 Elsevier Masson SAS. All rights reserved.